2022
DOI: 10.3390/jcm11154371
|View full text |Cite
|
Sign up to set email alerts
|

Metal Artifact Reduction Sequences MRI: A Useful Reference for Preoperative Diagnosis and Debridement Planning of Periprosthetic Joint Infection

Abstract: The diagnosis and treatment of periprosthetic joint infection (PJI) is complex and the use of MRI in PJI is gaining attention from orthopedic surgeons as MR technology continues to advance. This study aimed to investigate whether metal artefact reduction sequence (MARS) MRI could be used as an adjunct in the preoperative diagnosis of PJI and to explore its role in PJI debridement planning. From January 2020 to November 2021, participants with metal joint prostheses that needed to be judged for infection were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The metal artifact reduction sequence (MARS) was described by Olsen in 2000 [ 66 ]. Recent studies reported the usefulness of MARS for diagnosing periprosthetic infections of the shoulder [ 67 ] and hip and knee [ 68 ]. More advanced sequences for metal artifact reduction have been introduced, such as the view angle tilting (VAT) technique [ 69 ], WARP (a sequence commercialized by Siemens Healthcare, Erlangen, Germany) [ 65 ], slice encoding for metal artifact correction (SEMAC) [ 70 ], multi-acquisition variable-resonance image combination (MAVRIC) [ 71 ], and MAVRIC selective (MAVRIC SL) [ 72 ].…”
Section: Metal Artifact Reduction Strategiesmentioning
confidence: 99%
“…The metal artifact reduction sequence (MARS) was described by Olsen in 2000 [ 66 ]. Recent studies reported the usefulness of MARS for diagnosing periprosthetic infections of the shoulder [ 67 ] and hip and knee [ 68 ]. More advanced sequences for metal artifact reduction have been introduced, such as the view angle tilting (VAT) technique [ 69 ], WARP (a sequence commercialized by Siemens Healthcare, Erlangen, Germany) [ 65 ], slice encoding for metal artifact correction (SEMAC) [ 70 ], multi-acquisition variable-resonance image combination (MAVRIC) [ 71 ], and MAVRIC selective (MAVRIC SL) [ 72 ].…”
Section: Metal Artifact Reduction Strategiesmentioning
confidence: 99%
“…
The number of cases undergoing Total Knee Arthroplasty (TKA) has advanced manifolds in India and the role of Metal Artifacts Reduction Sequences (MARS) MRI is also gaining wide attention amongst Orthopaedicians/Radiologists for evaluation of painful knee after TKA or post TKA complications [1]. Here, we report a case of Patellar Clunk Syndrome (PCS) diagnosed on MRI with MARS sequence where the patient was also undertaken for Ultrasound for correlation.
…”
mentioning
confidence: 99%